Languages of Ethiopia and Languages of the 1994 Ethiopian Census - Hudson, Grover (Aethiopica, 2004)
The 1994 Population and Housing Census of Ethiopia gathered considerable information of linguistic interest, notably the number of speakers of seventy-seven languages which it recognized. The Census’s list is largely consistent with lists of languages recognized in current research by Ethiopianist linguists. However, problems of two sorts arise in the Census list: dialects counted as languages and languages counted as dialects. Survey of research in Ethiopian linguistics supports instead the existence of seventy-three Ethiopian languages now spoken, a list of languages and their dialects which includes varieties of speech recognized and unrecognized by the Census.